SOPHROLOGY AS A NEW MODEL FOR ACCOMPANIMENT OF AFRICAN MANAGERS, WHAT PROSPECTS? - Rabiae Saidi & Aziz Soulhi (International Journal of Research Science and Management, 2016)
The role of the manager within the company is not a long quiet river, purpose rather a turbulent river in which the manager must have the capacity for adaptation to live in harmony the permanent change or the only certainty that we can have is that the company will continue to change, especially with the digital transformation and artificial intelligence. The main purpose of our article consists in the proposal of a model of accompaniment of individual and collective based on sophrology. On the one hand for the control of stress within the company which is in constant evolution, on the other hand, to learn how to manage the change with serenity, develop self- confidence, and guide the intentionality toward the actions of the future by the techniques of relaxation dynamics of Caycedo.